A method for closed loop chemical recycling of a copolyester material
Patent Information
- Application Number
- CN202611063554.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-13
AI Technical Summary
水解法通常在强酸(如硫酸)或强碱(如氢氧化钠)催化下,于高温(>150℃)条件下进行,反应条件苛刻,处理成本高
[0016]本发明提供的共聚酯材料闭环化学回收利用的方法仅采用强碱、水和二醇在100℃以下、常压的温和条件下实现共聚酯材料高效解聚,解聚率>98%,得到的回收单体收率高、纯度高。并且,本发明利用回收单体能够直接合成再生共聚酯材料,其力学性能与原生共聚酯材料高度相似(拉伸强度和断裂伸长率保持率均超过95%),证明了回收单体的高品质以及本发明的闭环化学回收的循环可行性。本发明为共聚酯材料的绿色回收和再生利用提供了一条经济、环保、易于工业化的技术路径。
Smart Images

Figure CN122897975A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer material recycling technology, specifically relating to a closed-loop chemical recycling method for copolyester materials. Background Technology
[0002] Biodegradable polyester materials are widely used in packaging, agricultural films, disposable tableware, and express logistics. Among them, polybutylene succinate (PBS) and its modified copolymers have become an important alternative to traditional polyolefin materials due to their good biodegradability, thermal stability, and processing performance. However, the recycling and treatment processes for waste copolyester materials still have incomplete and immature aspects.
[0003] Currently, the mainstream recycling and disposal methods for waste copolyester materials are still landfill, composting, and incineration. While landfilling is simple to operate, the degradation cycle of copolyester materials in landfills is lengthy (usually requiring months or even years), occupies a large amount of land resources, and the resulting microplastics may seep into the soil and groundwater, posing long-term ecological risks. Composting, while in line with the design intent of biodegradable materials, faces many challenges in practice: firstly, household composting conditions cannot meet the temperature and humidity requirements of industrial composting, resulting in low degradation efficiency; secondly, the composting process converts the polymer's carbon skeleton into carbon dioxide, releasing it into the atmosphere, thus wasting carbon resources. Incineration can recover some heat energy, but the combustion of copolyester materials produces carbon dioxide and may be accompanied by the emission of other gaseous pollutants, exacerbating the greenhouse effect and air pollution.
[0004] The related technology discloses a closed-loop chemical recycling technique for treating copolyester materials. Currently, closed-loop chemical recycling methods for aliphatic copolyester materials (such as PBS) mainly include hydrolysis, alcoholysis, and enzymatic hydrolysis. Hydrolysis is typically carried out at high temperatures (>150°C) under strong acid (such as sulfuric acid) or strong base (such as sodium hydroxide) catalysis, resulting in harsh reaction conditions and high processing costs. Alcoholysis uses low-boiling-point alcohols (such as methanol or ethanol) as depolymerization reagents, adds a catalyst, and proceeds at reflux temperature. However, it suffers from the problems of low-boiling-point alcohols being flammable and explosive, difficulties in separating the catalyst from the product, and the need to add additional organic solvents (such as tetrahydrofuran or chloroform) to promote mass transfer. Enzymatic hydrolysis uses expensive enzyme catalysts, requires harsh reaction conditions, and its enzyme activity is easily inhibited by impurities and is difficult to reuse. Current recycling methods struggle to achieve efficient depolymerization of copolyester materials, resulting in low yields and purity of the depolymerized monomers. Summary of the Invention
[0005] The purpose of this invention is to provide a closed-loop chemical recycling method for copolyester materials. The method provided by this invention can achieve efficient depolymerization of copolyester materials, resulting in high yield and purity of the monomers obtained from the depolymerization.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A closed-loop chemical recycling method for copolyester materials includes the following steps: The copolyester material, strong alkali, water and glycol are mixed and subjected to a depolymerization reaction to obtain the depolymerized material. The depolymerized material is subjected to acidification and solid-liquid separation in sequence to obtain liquid material and solid material; The liquid and solid materials are respectively post-processed to obtain recovered monomers; The recycled monomer, 1,4-cyclohexanedicarboxylic acid and phthalate catalyst are mixed and then subjected to esterification and polycondensation reactions in sequence to obtain recycled copolyester material. The mass ratio of the strong alkali to the copolyester material is 0.9 to 1:1; the temperature of the depolymerization reaction is 95 to 100°C.
[0007] Preferably, the copolyester material is a polybutylene succinate copolyester material, and the raw materials for preparing the copolyester material include succinic acid monomer and 1,4-butanediol monomer, or include succinic acid monomer, 1,4-butanediol monomer and 1,4-cyclohexanedicarboxylic acid monomer.
[0008] Preferably, the molar ratio of succinic acid to 1,4-butanediol is 1:1.2~1.5; and the molar ratio of succinic acid monomer to 1,4-cyclohexanedicarboxylic acid monomer is 80~95:5~20.
[0009] Preferably, the strong alkali includes sodium hydroxide, the diol includes 1,4-butanediol, and the volume ratio of the diol to water is 1~1.2:1~1.2; the mass ratio of the copolyester material to the total volume of the diol and water is 1g:15~20mL.
[0010] Preferably, the depolymerization reaction takes 3-4 hours and is carried out under normal pressure.
[0011] Preferably, the acidification is carried out at a pH of 2 to 3, and the reagent used for acidification includes hydrochloric acid.
[0012] Preferably, the post-processing of the solid material includes washing and drying; the drying temperature is 50~60°C.
[0013] Preferably, the post-processing of the liquid material includes: vacuum distillation, wherein the vacuum distillation temperature is 120~125℃ and the pressure is 30~35mmHg.
[0014] Preferably, the recovered monomers include recovered succinic acid and recovered 1,4-butanediol.
[0015] Preferably, the esterification reaction is carried out at a temperature of 140~180℃ for 2~6h; the polycondensation reaction is carried out at a temperature of 210~230℃ for 4~8h.
[0016] The closed-loop chemical recycling method for copolyester materials provided by this invention utilizes only strong alkali, water, and glycol under mild conditions below 100°C and at normal pressure to achieve efficient depolymerization of copolyester materials, with a depolymerization rate >98%. The resulting recycled monomers have high yield and high purity. Furthermore, this invention can directly synthesize recycled copolyester materials using the recycled monomers, whose mechanical properties are highly similar to those of virgin copolyester materials (tensile strength and elongation at break retention rates both exceed 95%), demonstrating the high quality of the recycled monomers and the cyclical feasibility of the closed-loop chemical recycling method of this invention. This invention provides an economical, environmentally friendly, and easily industrialized technical path for the green recycling and reuse of copolyester materials.
[0017] Furthermore, the method provided by this invention has low energy consumption and simple equipment, requires no addition of any metal catalysts or enzymes, and uses only water and glycol in the reaction system without introducing any additional organic solvents. The yield of succinic acid recovery can reach over 87%, with a purity exceeding 98%; the yield of 1,4-butanediol recovery is higher than 88%, with a purity greater than 98%. Attached Figure Description
[0018] Figure 1 The succinic acid recovered in Example 1 of this invention 1 H NMR spectrum; Figure 2 This is a gas chromatogram of succinic acid recovered in Example 1 of the present invention; Figure 3 The 1,4-butanediol recovered in Example 1 of this invention 1 H NMR spectrum; Figure 4 The gas chromatogram of 1,4-butanediol recovered in Example 1 of the present invention; Figure 5 This is a stress-strain curve diagram of the recycled copolyester material and the original copolyester material in Example 2 of the present invention. Detailed Implementation
[0019] This invention provides a closed-loop chemical recycling method for copolyester materials, comprising the following steps: The copolyester material, strong alkali, water and glycol are mixed and subjected to a depolymerization reaction to obtain the depolymerized material. The depolymerized material is subjected to acidification and solid-liquid separation in sequence to obtain liquid material and solid material; The liquid and solid materials are respectively post-processed to obtain recovered monomers; The recycled monomer, 1,4-cyclohexanedicarboxylic acid and phthalate catalyst are mixed and then subjected to esterification and polycondensation reactions in sequence to obtain recycled copolyester material. The mass ratio of the strong alkali to the copolyester material is 0.9~1:1; the temperature of the depolymerization reaction is 95~100℃; the depolymerization reaction is carried out under normal pressure.
[0020] In this invention, unless otherwise specified, all raw materials / components used in the preparation are commercially available products well known to those skilled in the art.
[0021] This invention involves mixing a copolyester material, a strong alkali, water, and glycol, and then subjecting them to a depolymerization reaction to obtain a depolymerized material. In one embodiment of this invention, the copolyester material is a polybutylene succinate copolyester material. The raw materials for preparing the copolyester material include succinic acid monomer and 1,4-butanediol monomer, or include succinic acid monomer, 1,4-butanediol monomer, and 1,4-cyclohexanedicarboxylic acid monomer. The molar ratio of succinic acid to 1,4-butanediol is 1:1.2~1.5; the molar ratio of succinic acid monomer to 1,4-cyclohexanedicarboxylic acid monomer is 80~95:5~20, specifically 80:20; the 1,4-cyclohexanedicarboxylic acid monomer includes cis-1,4-cyclohexanedicarboxylic acid monomer, trans-1,4-cyclohexanedicarboxylic acid monomer, or a mixture of these configurations.
[0022] In one embodiment of the present invention, the strong alkali includes sodium hydroxide, and the mass ratio of the strong alkali to the copolyester material is 0.9~1:1, specifically 0.96:1. The present invention uses a strong alkali to promote the depolymerization reaction; by limiting the amount of strong alkali added, the copolyester material can be fully depolymerized.
[0023] In one embodiment of the present invention, the diol comprises 1,4-butanediol, and the water may be deionized water. The volume ratio of the diol to water is 1~1.2:1~1.2, specifically 1:1; the mass ratio of the copolyester material to the total volume of the diol and water is 1g:15~20mL. In this invention, the diol and water serve as solvents for the depolymerization reaction. The addition of the diol is crucial for the swelling and depolymerization of the copolyester material. The diol can reduce the viscosity of the reaction solution and promote the depolymerization reaction; the presence of water facilitates the OH- - Ionization promotes depolymerization reactions.
[0024] In one embodiment of the present invention, the depolymerization reaction is carried out under normal pressure, a protective atmosphere, and stirring conditions, wherein the protective atmosphere includes a nitrogen atmosphere; the temperature of the depolymerization reaction is 95~100℃, and the time is 3~4 hours; the heating rate from room temperature to the depolymerization reaction temperature is 10℃ / min. During the depolymerization reaction, the copolyester material gradually dissolves, and the reaction solution changes from turbid to a uniform transparent solution. In the present invention, the temperature of the depolymerization reaction has a significant impact on depolymerization. The depolymerization temperature defined in the present invention can ensure the occurrence of the depolymerization reaction while avoiding excessively high temperatures that could lead to the dehydration and cyclization of butanediol to form tetrahydrofuran.
[0025] After obtaining the depolymerized material, the present invention sequentially acidifies and separates the depolymerized material into liquid and solid materials. As one embodiment of the present invention, before acidification, the process further includes: cooling the depolymerized material to room temperature and performing vacuum distillation to obtain a concentrated solution; the vacuum distillation is performed in a rotary evaporator at a temperature of 60-65°C. The present invention removes water from the depolymerized material through vacuum distillation to obtain a concentrated solution.
[0026] In one embodiment of the present invention, the acidification is carried out at a pH of 2-3, and the reagent used for acidification includes hydrochloric acid. Preferably, the present invention involves adding hydrochloric acid to the dispersion under stirring conditions to adjust the pH to 2-3 to achieve acidification, and the concentration of the hydrochloric acid is 1M. The present invention precipitates succinic acid through acidification. The present invention then performs solid-liquid separation on the acidified mixture to obtain liquid and solid materials; the solid-liquid separation method can be filtration.
[0027] After obtaining the liquid and solid materials, the present invention performs post-processing on the liquid and solid materials respectively to obtain recovered monomers. In one embodiment of the present invention, the post-processing of the solid material includes: washing and drying; the washing solvent is water, specifically cold water; the drying can be vacuum drying, and the drying temperature is 50-60°C; the recovered monomer obtained from the post-processing of the solid material is recovered succinic acid. The yield of the recovered succinic acid is ≥87%, and the purity is ≥98%.
[0028] In one embodiment of the present invention, the post-processing of the liquid material includes: vacuum distillation, wherein the vacuum distillation temperature is 120~125℃ and the pressure is 30~35 mmHg; the recovered monomer obtained from the post-processing of the liquid material is recovered 1,4-butanediol. The yield of the recovered 1,4-butanediol is ≥88%, and the purity is ≥98%.
[0029] In the closed-loop chemical recycling method for copolyester materials disclosed in this invention, the 1,4-cyclohexanedicarboxylic acid monomer, due to its low content and relatively higher solubility than succinic acid, does not reach its saturation precipitation point and remains in the liquid material after acidification. The liquid material undergoes vacuum distillation to recover only 1,4-butanediol; 1,4-cyclohexanedicarboxylic acid, due to its much higher boiling point than 1,4-butanediol, remains in the distillation residue. Therefore, 1,4-cyclohexanedicarboxylic acid neither precipitates as a solid with succinic acid nor distills off with 1,4-butanediol, but is enriched in the distillation residue. Since this invention only requires the recovery of succinic acid and 1,4-butanediol to achieve repolymerization, no additional separation of 1,4-cyclohexanedicarboxylic acid is required, thus simplifying the recycling process and reducing energy consumption and costs.
[0030] The present invention mixes the recovered monomer, 1,4-cyclohexanedicarboxylic acid and phthalate catalyst, and performs esterification and polycondensation reactions sequentially to obtain a recycled copolyester material. In one embodiment of the present invention, the recovered monomers include recovered succinic acid and recovered 1,4-butanediol, wherein the 1,4-cyclohexanedicarboxylic acid is cis-1,4-cyclohexanedicarboxylic acid, and the phthalate catalyst includes tetrabutyl titanate; the molar ratio of the recovered succinic acid, recovered 1,4-butanediol, and 1,4-cyclohexanedicarboxylic acid is 0.08~0.095:0.12~0.15:0.005~0.02; the mass of the catalyst is 0.05% of the total mass of the recovered succinic acid and 1,4-cyclohexanedicarboxylic acid; the esterification reaction is carried out at a temperature of 140~180℃, specifically 160℃, for a time of 2~6 hours, specifically 4 hours, under nitrogen protection; the polycondensation reaction is carried out at a temperature of 210~230℃, for a time of 4~8 hours, specifically 6 hours, under vacuum conditions to a pressure below 100 Pa.
[0031] To further illustrate the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments thereof. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0032] The copolyester material used in the following experiments of this invention is PBSC. 20-c The copolyester material, PBSC 20-c The preparation method of copolyester material includes the following steps: Under nitrogen protection, succinic acid (0.80 mol, 94.5 g), 1,4-butanediol (1.2 mol, 108.1 g), and cis-1,4-cyclohexanedicarboxylic acid (0.20 mol, 34.4 g) were added to a 500 mL three-necked flask. The molar amount of cis-1,4-cyclohexanedicarboxylic acid was 5% of the total molar amount of succinic acid and cis-1,4-cyclohexanedicarboxylic acid. 0.06 g of tetrabutyl titanate was added to the reaction system. The mass of tetrabutyl titanate was equal to the molar amount of succinic acid and cis-1,4-cyclohexanedicarboxylic acid. 0.05% of the total mass of 4-cyclohexanedicarboxylic acid was added; the temperature was increased from room temperature to 160°C at a rate of 10°C / min, and esterification was carried out for 4 hours under normal pressure and mechanical stirring to obtain a prepolymer; the temperature was increased from 160°C to 210°C at a rate of 10°C / min, and vacuum was applied to a pressure below 100 Pa, and the prepolymer was subjected to polycondensation for 6 hours to obtain a molten polyester material; the molten polyester material was cooled to room temperature, pulverized, and granulated to obtain a copolyester material denoted as PBSC. 20-c .
[0033] Example 1 Take PBSC 20-c 10.0 g of copolyester material, 9.6 g of sodium hydroxide (mass ratio of sodium hydroxide to copolyester material was 0.96:1), 30 mL of deionized water, and 30 mL of 1,4-butanediol were added to a 250 mL round-bottom flask. Under nitrogen protection and normal pressure, mechanical stirring was started, and the temperature was increased from room temperature to 95 °C at a rate of 10 °C / min for 4 h of depolymerization reaction. After the reaction was completed, the mixture was cooled to room temperature. The reaction solution was transferred to a rotary evaporator and distilled under reduced pressure at 60 °C to obtain a concentrated solution. Under stirring, 1 M hydrochloric acid was added to the concentrated solution to adjust the pH to 2, resulting in precipitation. The resulting mixture was vacuum filtered to obtain liquid and solid materials. The solid material was washed with cold water and vacuum dried at 50 °C to constant weight to obtain recovered succinic acid (r-SA) with a yield of 87.2% and a purity of 98.5% determined by high performance liquid chromatography (HPLC).
[0034] The liquid material (containing 1,4-butanediol and water) was distilled under reduced pressure at 120°C and 30 mmHg. The fraction was collected to obtain recovered 1,4-butanediol (r-BDO), which was a colorless liquid with a yield of 88.6% and a purity of 98.3% determined by gas chromatography (GC).
[0035] Example 2: Regenerated copolyester material (r-PBSC) 20-c Preparation of ) 0.08 mol of recovered succinic acid, 0.12 mol of recovered 1,4-butanediol, and 0.02 mol of cis-1,4-cyclohexanedicarboxylic acid (purchased from Aladdin Reagent (Shanghai) Co., Ltd.) obtained in Example 1 were added to a reactor, along with tetrabutyl titanate as a catalyst (the mass of tetrabutyl titanate was 0.05% of the total mass of succinic acid and cis-cyclohexanedicarboxylic acid). Under nitrogen protection, the temperature was raised to 160°C, and the esterification reaction was carried out at atmospheric pressure for 4 hours. Water was removed using a water separator. Then, the reaction system was heated to 210°C, and a vacuum was drawn until the pressure was below 100 Pa for a polycondensation reaction for 6 hours. After the reaction was completed, the molten reaction product was cooled to obtain a recycled copolyester material, denoted as r-PBSC. 20-c .
[0036] Comparative Example 1: No alkali added It is basically the same as Example 1, except that sodium hydroxide is not added.
[0037] Comparative Example 2: Only a single deionized water solvent was added The method is basically the same as in Example 1, except that only 60 mL of deionized water is added and 1,4-butanediol is not added.
[0038] Comparative Example 3: Only 1,4-butanediol solvent was added The procedure is essentially the same as in Example 1, except that only 60 mL of 1,4-butanediol is added, and deionized water is not added.
[0039] Comparative Example 4: Low Temperature Conditions It is basically the same as Example 1, except that the temperature of the depolymerization reaction is 80°C.
[0040] Comparative Example 5: Low Alkali Content Conditions The method is basically the same as in Example 1, except that the amount of sodium hydroxide added is 4.0g (the mass ratio of sodium hydroxide to copolyester material is 0.4:1).
[0041] Test Example 1: Proton NMR Spectroscopy (NMR) 1 H NMR test The recovered monomers were structurally characterized using a Bruker AVANCE III HD-400 nuclear magnetic resonance spectrometer (400 MHz). The structure of the recovered monomers was verified by characteristic peaks using deuterated chloroform (CDCl3) as solvent and tetramethylsilane (TMS) as an internal standard. The results are as follows: Figure 1 and Figure 3 As shown.
[0042] Figure 1 The succinic acid recovered in Example 1 of this invention 1 H NMR spectrum, based on Figure 1It can be seen that the broad peak at chemical shift δ=12.10ppm belongs to carboxyl protons (-COOH), and the single peak at δ=2.30ppm belongs to methylene protons (-CH2-CH2-), which is completely consistent with the succinic acid standard spectrum. No other impurity peaks were detected, indicating that the product has high purity.
[0043] Figure 3 The 1,4-butanediol recovered in Example 1 of this invention 1 H NMR spectrum, based on Figure 3 It can be seen that the characteristic peaks of chemical shift δ=4.45ppm (t, 2H, -OH), δ=3.44ppm (t, 4H, -CH2-OH), and δ=1.52ppm (m, 4H, -CH2-CH2-) are consistent with those of 1,4-butanediol standard, with no additional signal, proving that the structure is intact.
[0044] Test Example 2: High Performance Liquid Chromatography (HPLC) Test The purity of succinic acid was determined by high-performance liquid chromatography (HPLC). The HPLC conditions were as follows: a C18 column was used; the mobile phase was 0.1% phosphoric acid / water / methanol (95:5); the flow rate was 1.0 mL / min; and the UV detection wavelength was 210 nm. The results are as follows: Figure 2 As shown.
[0045] Figure 2 This is a gas chromatogram of succinic acid recovered in Example 1 of the present invention. Figure 2 It can be seen that the retention time of the main peak is basically consistent with that of the succinic acid standard. Calculated by the area normalization method, the purity of the recovered succinic acid is 98.5%, and no obvious impurity peaks were detected.
[0046] Test Example 3: Gas Chromatography (GC) Test The purity of 1,4-butanediol was determined by gas chromatography (GC). The GC conditions were: SE-54 capillary column (30 m × 0.32 mm × 0.25 μm), FID detector, and programmed temperature control: initial temperature 60 °C, held for 3 min, then increased to 240 °C at a rate of 20 °C / min and held for 5 min. The results are as follows: Figure 4 As shown.
[0047] Figure 4 This is the gas chromatogram of 1,4-butanediol recovered in Example 1 of the present invention. Figure 4 It can be seen that the retention time of the main peak is basically the same as that of the 1,4-butanediol standard. The main peak area accounts for 98.3%, containing only trace amounts of water and a very small amount of by-products, which meets the requirements for repolymerization.
[0048] Test Example 4: Mechanical Property Test The tensile properties of the recycled copolyester material prepared in Example 2 were tested using a universal testing machine according to GB / T 1040.4-2006 standard. The samples were injection-molded 2A dumbbell-shaped strips. The test temperature was room temperature, and the tensile rate was 50 mm / min. At least five parallel samples were tested for each sample, and the average value was recorded. The tensile strength and elongation at break were recorded. The results are as follows: Figure 5 As shown.
[0049] Figure 5 The figures show the stress-strain curves of the recycled copolyester material and the virgin copolyester material in Example 2 of this invention. The two curves are basically overlapping, indicating that the mechanical properties of the recycled copolyester material are highly similar to those of the virgin copolyester material.
[0050] Test Example 5: Depolymerization Rate Test The weight depolymerization rate of Example 1 and Comparative Examples 1-5 was calculated according to the formula: Where M1 is the initial mass and M2 is the mass after alcoholysis.
[0051] The copolyester material of the present invention has a depolymerization rate of 98%; the copolyester material of Comparative Example 1 is almost insoluble and has a depolymerization rate of less than 5%; proving that alkali is a necessary condition for the depolymerization reaction.
[0052] The reaction solution in Comparative Example 2 was viscous, the copolyester material was not completely dissolved, the depolymerization rate was 35%, and the product after acidification was difficult to filter; this proves that the addition of BDO is crucial to the swelling and depolymerization of the copolyester material.
[0053] The copolyester material in Comparative Example 3 had a depolymerization rate of 65%, but the reaction system had high viscosity and uneven mass transfer, making subsequent distillation separation difficult; this demonstrates that the presence of an appropriate amount of water helps OH... - Ionization promotes depolymerization reactions.
[0054] The depolymerization rate of the copolyester material in Comparative Example 4 was 32%, demonstrating that a suitable temperature is a necessary condition for achieving efficient depolymerization.
[0055] The depolymerization rate of the polyester material in Comparative Example 5 was 48%, proving that depolymerization is insufficient when the alkali content is insufficient.
[0056] In summary, the closed-loop chemical recycling method for copolyester materials provided by this invention achieves highly efficient depolymerization (>98%) and high-yield, high-purity recovery of monomers without the need for catalysts or organic solvents. The recovered monomers can be directly repolymerized while maintaining good performance. The method of this invention is simple, operates under mild conditions, and is low-cost, possessing broad prospects for industrial application.
[0057] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. Furthermore, those skilled in the art will recognize that, based on the ideas of the present invention, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A method for closed-loop chemical recycling of copolyester materials, comprising the following steps: The copolyester material, strong alkali, water and glycol are mixed and subjected to a depolymerization reaction to obtain the depolymerized material. The depolymerized material is subjected to acidification and solid-liquid separation in sequence to obtain liquid material and solid material; The liquid and solid materials are respectively post-processed to obtain recovered monomers; The recycled monomer, 1,4-cyclohexanedicarboxylic acid and phthalate catalyst are mixed and then subjected to esterification and polycondensation reactions in sequence to obtain recycled copolyester material. The mass ratio of the strong alkali to the copolyester material is 0.9 to 1:1; the temperature of the depolymerization reaction is 95 to 100°C.
2. The method according to claim 1, characterized in that, The copolyester material is a polybutylene succinate copolyester material. The raw materials for preparing the copolyester material include succinic acid monomer and 1,4-butanediol monomer, or include succinic acid monomer, 1,4-butanediol monomer and 1,4-cyclohexanedicarboxylic acid monomer.
3. The method according to claim 2, characterized in that, The molar ratio of succinic acid to 1,4-butanediol is 1:1.2~1.5; the molar ratio of succinic acid monomer to 1,4-cyclohexanedicarboxylic acid monomer is 80~95:5~20.
4. The method according to claim 1, characterized in that, The strong base includes sodium hydroxide, the diol includes 1,4-butanediol, and the volume ratio of the diol to water is 1~1.2:1~1.2; the mass ratio of the copolyester material to the total volume of the diol and water is 1g:15~20mL.
5. The method according to claim 1, characterized in that, The depolymerization reaction takes 3-4 hours and is carried out under normal pressure.
6. The method according to claim 1, characterized in that, The acidification is carried out at a pH of 2 to 3, and the reagents used for acidification include hydrochloric acid.
7. The method according to claim 1, characterized in that, The post-processing of the solid material includes washing and drying; the drying temperature is 50~60℃.
8. The method according to claim 1, characterized in that, The post-processing of the liquid material includes vacuum distillation, wherein the vacuum distillation temperature is 120~125℃ and the pressure is 30~35mmHg.
9. The method according to any one of claims 1 to 8, characterized in that, The recovered monomers include recovered succinic acid and recovered 1,4-butanediol.
10. The method according to claim 1, characterized in that, The esterification reaction is carried out at a temperature of 140~180℃ for 2~6h; the polycondensation reaction is carried out at a temperature of 210~230℃ for 4~8h.